Biofertilization with beneficial microorganisms and low rates of chemical fertilization in potatoes (Solanum tuberosum L.) management for sustainable agriculture - R. H. Tirado-Malaver; R. Tirado-Lara (Brazilian Journal of Biology)
Abstract Potato is considered one of the most important crops in the world. However, biotic and abiotic factors can considerably affect the production of this crop and increase production costs, the biofertilizers are environmentally friendly alternatives that could reduce these problems. The objective was to determine the biofertilizer activity of Trichoderma harzianum and Bacillus subtilis as a sustainable alternative to reduce chemical fertilization in potato productivity. In this research, two potato varieties (commercial variety Yungay and the improved variety 302295.32), two beneficial microorganisms (Trichoderma harzianum and Bacillus subtilis both at a dose of 1 kg ha-1) and three doses of chemical fertilization (20, 50 and 100% NPK) and a control (commercial variety Yungay at a dose of 100% NPK) were used in a 2x2x3+1 factorial scheme. The findings obtained reported that the use of the variety CIP302295.32 biofertilized with T. harzianum can obtain similar results using less chemical fertilizers compared to high NPK doses. The highest biometric parameters in potato were achieved in the treatments, variety CIP 302290.11 inoculated with T. harzianum at doses of 50 and 100% of NPK, so that at a dose 50% less fertilizer produced an increase of 24. 39% in the number of tubers per plant compared to the control and in the number of commercial tubers per plant the increase was 50.31%. This same treatment had a significant effect on yield parameters, increasing by 42.17% in total yield and 49.09% in commercial yield compared to the control. Therefore, this research demonstrated that biofertilization of the improved variety 302295.32 with T. harzianum at a dose of 50% NPK is a valuable alternative to increase the yield of sustainable potato cultivation in Peruvian Andean.